Pengaruh Perceived Usefulness, Perceived Easy Of Use, Perceived Risk, Dan Perceived Compatibility Terhadap Proses Keputusan Nasabah Menggunakan Mobile Banking Bank Syariah Indonesia (Studi Kasus Nasabah Bank Syariah Indonesia KCP Medan Marelan) - Ayu Elvina; Nur Ahmadi Bi Rahmani (Jurnal Ilmiah Ekonomi Islam, 2023)
The purpose of this study was to explain and analyze the influence of perceived usefulness, perceived ease of use, perceived risk and perceived compatibility on customer decision processes using Bank Syariah Indonesia's mobile banking. This study uses quantitative methods and data collection through questionnaires, the population of which is the customer of Bank Syariah Indonesia KCP Medan Marelam, while the sample taken is 65 respondents. The results of the study with the t test showed that the variables perceived usefulness separately did not have a significant effect on customers' decisions to use mobile banking, while the variables perceived ease of use, perceived risk and perceived compatibiliy showed that these variables had a significant effect on customers' decisions to use mobile banking. The results of the F test show that the variables perceived usefulness, perceived ease of use, perceived risk and perceived suitability simultaneously have a significant effect on customers' decisions to use mobile banking. The magnitude of the influence of perceived usefulness, perceived ease of use, perceived risk and perceived suitability of the customer's decision to use mobile banking is 72.8%, while the rest is influenced by other variables.